Public Expenditures and their Effects on Economic Stability "The ninth five-year plan in the Sultanate of Oman 2016-2020, an applied sample - Al-Awaid, Musallam Salim Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
The researcher dealt with this topic entitled: Public expenditures and their effects on economic stability in two sections, the first topic entitled: The concept and legality of public expenditures and its elements, and the second topic entitled: The effects of public expenditures on economic stability, then the research concluded with the most important findings and recommendations that the researcher reached, and here we review The most important findings and recommendations are as follows: 1. In no case can legitimacy be overridden in the matter of public expenditures. The legislative authority works to approve aspects of public spending, where the ruler, the ruled, and the three authorities are subject to the principle of legitimacy in the state of law and institutions. 2. Countries seek to keep abreast of global developments in various fields, and thus the volume of expenditures increases annually, and the risk of resorting to borrowing has an impact on the economic stability of countries that may reach the threat of their existence in the event that studied principles are not followed to invest those loans. 3. As long as the ruling regime does not work to curb its desires for public expenditures, the matter warns of a danger through the financial deficits that are generated as a result of those expenditures, while relying on one resource, which is oil, and this is what we noticed in the ninth five-year plan.